2017
DOI: 10.1073/pnas.1611891114
|View full text |Cite
|
Sign up to set email alerts
|

Prion replication without host adaptation during interspecies transmissions

Abstract: Adaptation of prions to new species is thought to reflect the capacity of the host-encoded cellular form of the prion protein (PrPC) to selectively propagate optimized prion conformations from larger ensembles generated in the species of origin. Here we describe an alternate replicative process, termed nonadaptive prion amplification (NAPA), in which dominant conformers bypass this requirement during particular interspecies transmissions. To model susceptibility of horses to prions, we produced transgenic (Tg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 54 publications
(77 reference statements)
2
55
0
Order By: Relevance
“…Mw: Molecular weight amplification without adaptation to the new host but conserving its pathobiological features toward a host with the original cattle PrP C , similar to that described previously for other isolate-host combination such as scrapie in TgHorse mice. 21 The possible relevance of the negatively charged amino acid residue in position 163 of dog PrP to their resistance to prion infection was initially suspected from sequence alignment studies of the PRNP of several members of the canidae family with those of susceptible species. These studies revealed that feline PrP was the most similar in terms of amino acid sequence and as domestic cats are susceptible to at least three known prion strains (BSE, CWD, and CJD) 26,[44][45][46] the six amino acid difference between canine and feline PrP was studied in detail.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mw: Molecular weight amplification without adaptation to the new host but conserving its pathobiological features toward a host with the original cattle PrP C , similar to that described previously for other isolate-host combination such as scrapie in TgHorse mice. 21 The possible relevance of the negatively charged amino acid residue in position 163 of dog PrP to their resistance to prion infection was initially suspected from sequence alignment studies of the PRNP of several members of the canidae family with those of susceptible species. These studies revealed that feline PrP was the most similar in terms of amino acid sequence and as domestic cats are susceptible to at least three known prion strains (BSE, CWD, and CJD) 26,[44][45][46] the six amino acid difference between canine and feline PrP was studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons that might explain why species that have been experimentally proven susceptible to prion disease have never had naturally occurring cases reported. These include pigs, rabbits, mice, nonhuman primates, ferrets, and even horses where a transgenic mouse model with equine PrP was used …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, conformations of M129-compatible PrP Sc and V129-compatible PrP Sc should be sufficiently different accordingly. Interestingly, the traits of V129-compatible PrP Sc are so stable that they are preserved through passages to M129-PrP-expressing individuals, without abbreviation of incubation periods on the secondary transmissions, i.e., no adaptation to M129-PrP [19][20][21], reminiscent of non-adaptive prion amplification, NAPA [22]. This was in contrast with ordinary species barriers accompanied by adaptation to the new host, e.g., transmission of Syrian hamster scrapie to Chinese hamsters [23].…”
Section: Introductionmentioning
confidence: 99%